Microbiological Study of the Oral Cavity in Patients with Chronic Kidney Disease Wearing Removable Partial Dentures - Rikhsiyeva D.U (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The study investigates the dynamics of microbial colonization on removable dentures made from different base materials — acrylic and thermoplastic (nylon). Microbiological analysis demonstrated that, over time, dentures become colonized by microorganisms; however, the level of contamination was significantly higher in acrylic dentures compared to thermoplastic ones. This finding is explained by the structural differences between materials, as acrylic resin possesses higher porosity, facilitating bacterial adhesion and biofilm formation. The theoretical significance of the research lies in its contribution to understanding the nonspecific protective mechanisms of the oral mucosa and the influence of denture base materials on oral microbiocenosis. The results provide insight into the early stages of inflammatory processes and prosthesis intolerance associated with microbial colonization, emphasizing the importance of selecting biocompatible materials and maintaining proper oral hygiene. The study’s outcomes can serve as a foundation for developing preventive strategies to improve the biological performance of removable dentures.